Про Белзьке князівство Юрія Наримунтовича (1352-1377) - Козубовський, Г.А. (Археологія, 2014)
Окреслено значення одного із князівств Галицької землі в XIV ст. Западная Волынь и Холмщина в Хiv в. занимали важнейшее геополитическое положение в отношениях между Польшей, Мазовией, русскими и литовскими княжествами, Золотой Ордой. В 1352—1377 гг. здесь существовало Белзское княжество Юрия Наримунтовича.
На основе письменных, археологических и нумизматических источников рассмотрены спорные вопросы истории Белзской земли второй половины Xiv в. Здесь в 1350—1370 гг. были в обращении пражские гроши Яна i Люксембургского (1310—1346), Карла І (1346—1378), серебряные монеты ханов Золотой Орды Бердибека (1357— 1359) и Мухаммеда Буляка (1370—1380), польские квартники Казимира iii (1333—1370) и галицкорусские моне ты Владислава Опольского (1372—1379).
Через Белзское княжество пражские гроши поступали на территорию Волыни, Галиции и Литвы многими путями. Находки пражских грошей на территории Белзского и в западной части Волынского княжеств указывают на торговые связи с землями, где обращалась такая монета в середине Хiv в.: Малопольшей, Галицией, Мазо вией, Великопольшей. Стимулом для экономического и политического развития Западной руси были торговые соляные пути в бассейне Буга. Белз был активным центром соляной торговли, через него проходили важнейшие международные торговые пути. Western volyn and kholm region occupied an important geopolitical place in relations between Poland, Mazovia, rus sian and lithuanian kingdoms, and the Golden horde in the 14th c. Belz kingdom of yuriy narymuntovych existed here in 1352—1377.
Based on written, archaeological, and numismatic sources, the disputable issues on Belz land history at the end of the 14th c. are discussed. Prague groschen of John i Count of luxembourg (1310—1346), Charles iv (1346—1378), silver coins of Golden horde khans Berdi Beg (1357—1359) and Mohammad Bolak (1370—1380), Polish kwartniks of kazimierz iii (1333—1370), and Galicianrus coins of vladislaus of Opole (1372—1379) were in circulation here in 1350—1370.
Prague groschen arrived onto the territory of volyn, Galicia, and lithuania via Belz kingdom by many routs. Finds of Prague groschen on the territory of Belz kingdom and in the western part of volyn kingdom evidence for the trade relations with the areas where such coin was used in the middle 14th c.: lesser Poland, Galicia, Mazovie, and Greater Poland. trade salt routs in the Buh river basin was the factor that stimulated the economic and political development of Western rus. Belz was an active centre of salt market, and the important international trade routs passed through it.